Distribution of methanogenic and methanotrophic consortia at soil-water interfaces in rice paddies across climate zones - Sichu Wang; Pengfei Sun; Junzhuo Liu; Ying Xu; Jan Dolfing; Yonghong Wu (iScience, 2023)
Summary: Periphytic biofilms (PB) at the soil-water interface contributes 7–38% of the methane emission from rice paddies, yet the biogeographical mechanism underlying and affecting the process remain elusive. In this study, rice fields along an edapho-vclimatic gradient were sampled, and the environmental drivers affecting distribution of methanogenic and methanotrophic communities were evaluated. The methanogenic and methanotrophic communities at soil-water interface showed less complex inter/intra-generic interactions than those in soil, and their relative abundances were weakly driven by spatial distance, soil organic carbon, soil total nitrogen and pH. The nutrient supply and buffering capacity of extracellular polymeric substance released by PB reduced their interaction and enhanced the resilience on edaphic environment changes. Climate affected soil metal content, extracellular polymeric substance content, and thus the methane-related communities, and caused geographical variation in the impacts of PB on methane emissions from rice paddies. This study facilitates our understanding of geographical differences in the contribution of PB to methane emission.